2021
DOI: 10.1016/j.soard.2021.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric and metabolic surgery in patients with morbid obesity and multiple sclerosis - a nationwide, matched cohort study

Abstract: Background: Despite an association between obesity and multiple sclerosis (MS), very little is known regarding the safety and efficacy outcomes for patients with MS and severe obesity undergoing metabolic surgery. Objectives: The aim of the present study was to evaluate early complications and efficacy outcomes of metabolic surgery in patients with severe obesity and MS. Setting: Nationwide, Sweden. Methods: In this, matched cohort study, 196 patients with an MS diagnosis in the Swedish MS register who were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…7,15 Therefore, the negative effect of metabolic surgery on disability in comparison with matched MS controls is a disappointing one, given that the surgery was both safe and efficient in meeting its goals in terms of weight loss. 9 The exact mechanisms behind our findings are speculative. It is possible that the clinical course of the disease is negatively affected due to nutritional deficiencies and changes in the gut permeability, and possibly also by changes in the hormonal balance and a shift in the proinflammatory cytokine profile.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7,15 Therefore, the negative effect of metabolic surgery on disability in comparison with matched MS controls is a disappointing one, given that the surgery was both safe and efficient in meeting its goals in terms of weight loss. 9 The exact mechanisms behind our findings are speculative. It is possible that the clinical course of the disease is negatively affected due to nutritional deficiencies and changes in the gut permeability, and possibly also by changes in the hormonal balance and a shift in the proinflammatory cytokine profile.…”
Section: Discussionmentioning
confidence: 92%
“…A substantial decrease in metabolic comorbidities has been reported following metabolic surgery 7 as well as reduced general inflammation. 8 We have previously evaluated early complications and efficacy outcomes of bariatric surgery in severely obese patients with and without MS. 9 No major differences were observed regarding the rate of postoperative complications, and weight loss at 2 years following surgery was similar in patients with MS and controls. However, it is unclear how bariatric procedures affect the activity and progression of MS. A small case-control study (n = 16) evaluating the walking outcome as measured by the timed twentyfive-foot walk test found that MS patients who had undergone metabolic surgery maintained their walking speed, while controls were about 2 seconds slower on average at follow-up.…”
Section: Introductionmentioning
confidence: 86%
“…Data from SOReg and the Swedish multiple sclerosis registry have demonstrated that bariatric surgery is safe in patients with multiple sclerosis and results in improvements in health-related quality of life. 79 However, the time to 6-month confirmed disability progression during the first 5 years after baseline was shorter among the surgical patients (HR 2.31). No differences were observed regarding postoperative annual relapse rate or time to first postoperative relapse.…”
Section: Effect On Other Conditionsmentioning
confidence: 88%
“…However, weight loss may convey significant benefits in terms of mobility. Data from SOReg and the Swedish multiple sclerosis registry have demonstrated that bariatric surgery is safe in patients with multiple sclerosis and results in improvements in health‐related quality of life 79 . However, the time to 6‐month confirmed disability progression during the first 5 years after baseline was shorter among the surgical patients (HR 2.31).…”
Section: Effect On Obesity‐related Diseases and Other Conditionsmentioning
confidence: 99%
“…This matched cohort study revealed that postoperative complications did not differ between the two groups and the surgery was safe and improved quality of life in PwMS. 27 …”
Section: Discussionmentioning
confidence: 99%